Identification Of Potassium, Organic Carbon and Soil Ph on Sloping Land of Cabbage Crops at Agrotourism Area Rurukan Sub-District - Bubun, Priskila Meilany Ruga; Theffie, Karamoy Lientje; Kawulusan, Rafli Irland (Soil and Environment Journal, 2024)
This study aims to identify nutrient levels of potassium, organic carbon and soil pH on sloping land of cabbage crops at agrotourism. area, rurukan sub-district. The method used in this study is a descriptive method whose implementation is field surveys to ensure the three sampling points, samples taken from different slopes and representing each slope; upper slope (LA), middle slope (LT), and lower slope (LB). Sampling of soil at a 0-20 cm depth in the soil. Parameters observed included the availability of potassium (Bray I method), organic carbon (Walkley and Black method), and soil pH (H2O using pH meter). The results of laboratory analysis showed sequential values on the upper slope, the middle slope, and the lower slope available potassium varied, 30.11 ppm; 27.11 ppm; and 31.67 ppm, the organic carbon value is relatively high, 3.27%; 3.20%; 4.78% and the unit value of soil pH is classified as neutral, 6.72; 6.69; 6,79. Keywords: sloping land, plant available nutrient, Rurukan agrotourism area Abstrak Penelitian ini bertujuan untuk mengidentifikasi kadar hara kalium, karbon organik, dan pH tanah pada lahan miring pertanaman kubis di kawasan agrowisata Kecamatan Rurukan. Metode yang digunakan dalam penelitian ini adalah metode deskriptif yang pelaksanaannya adalah survei lapangan untuk memastikan tiga titik pengambilan sampel, sampel diambil dari lereng yang berbeda dan mewakili masing-masing lereng; lereng atas (LA), lereng tengah (LT), dan lereng bawah (LB). Pengambilan sampel tanah pada kedalaman 0-20 cm di dalam tanah. Parameter yang diamati meliputi ketersediaan kalium (metode Bray I), karbon organik (metode Walkley dan Black), dan pH tanah (H2O menggunakan pH meter). Hasil analisis laboratorium menunjukkan nilai berurutan pada lereng atas, lereng tengah, dan lereng bawah kalium tersedia bervariasi, 30,11 ppm; 27,11 ppm; dan 31,67 ppm, nilai karbon organik relatif tinggi, 3,27%; 3,20%; 4,78% dan nilai satuan pH tanah tergolong netral, 6,72; 6.69; 6,79. Kata kunci: lahan miring, ketersediaan hara tanaman, kawasan agrowisata Rurukan